Memorandum of understanding between Universiti Teknologi MARA and Rangsit Universitu (RSU) / Fakulti Muzik - Universiti Teknologi MARA, Fakulti Muzik (Universiti Teknologi MARA (UiTM), 2021)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.